Phosphors for White LED Conversion - Abd, Husnen R.; Hassan, Z.; Ahmed, Naser M.; Chin, C. W.; Yusof, Ahmad Sauffi; AI-Hazeem, Nabeel Z. (2016)
White light emission from blue lnGaN LED chip (WLED) was fabricated by converting blue co lour using phosphor. Yttrium aluminium garnet (YAG, Y3Al5O12) is an important phosphor having applications in various fields ranging from solid state lighling to scintillation detectors. Yttrium nitrate and aluminium nitrate phosphor doped with cerium nitrate (activator) according to the formu la, Y (J-0 06) Al5O12: oo6 ce+3 (YAG: ce+3) and mixed with urea ( fuels) are synthesized by microwave-oven technique (M. W). The sintering temperature for enriching nanoparticles was achieved at 1050°C for 5 hours. The crystallinity, structure morphology, luminescent properties with fixed currents densities (20mA) and chromaticity parameters were charac terized by X-ray di ffraction (XRD), field emission-scanning electron microscope (FE-SEM), electroluminescence (EL) and standard ClE 1931 chromaticity diagram, respectively. By controlling the composition and chemical structures of Y AG: Ce mi xed wi th epoxy resin, white light with a broad band luminescent spectrum, best color rendering index (CRI ), and tunable correlated color temperature (CCT) were obtained, offering cool white.